SEARCH FOR CHARACTER EDUCATION CONCEPT AND IMPLEMENTATION IN INDONESIA - Ismail Marzuki (International Journal of Education, Information Technology, and Others, 2018)
Indonesia is located in Asia, known as the people who have local knowledge and friendliness. Indonesian society is also known as an open society, a fact plurality Indonesian society from aspects of beliefs, customs, culture is also a language is evidence of diverse cultures have entered and later became joint Indonesian society. However, over the wisdom of this nation as if fading, eroded by age increasingly rattling pace. It is well known, education is an important element influential in shaping the pattern of community life. The concept of moral education, moral, ethical and moral is always the basis of education, both formal and non-formal. Character education, a concept that is offered on the phenomena that occur at this time. Essence and character education has the same meaning as moral education and moral education. The goal is to establish a personal Child, so that a good human being, citizens, and good citizens. The criteria for good men, good citizens, and good for the citizens of a community or nation, in general are certain social values ​​are influenced by the culture of the community and nation. Thus, the essence of character education in the context of education in Indonesia is the value of education, namely education noble values ​​originating from the culture of the nation itself, in order to nurture the younger generation's personality.